Zestawienie jako narzędzie dziennikarskiej perswazji - Siekiera, Rafał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The article aims to demonstrate the way in which juxtaposition-comparison (as defined by Andrzej Kudra as a basic mental figure) is used by journalists for persuasive purposes. An analysis of selected examples reveals that various forms of juxtapositions are used by serial writers (comparisons of Poland with other countries, gradual confrontations, ridiculing and revealing absurdities through juxtapositions, comparisons of a current situation with the past, juxtapositions emphasizing people’s defects or advantages). In each case, the authors make use of the imagery qualities of juxtapositions, their ability to transfer axiological valuation from comparans to comparandum, as well as their ability to profile features through comparison.